Childhood obesity and parental reflective functioning: Is there a relation? - Pazzagli, Chiara (Int J Clin Health Psychol, 2019)
BACKGROUND/OBJECTIVE: In recent decades, the prevalence of childhood obesity has increased, with the major implications for public health. However, the factors that contribute to obesity in children are still poorly understood. The present study aimed to investigate the role of parental reflective functioning (PRF) in childhood obesity. METHOD: In a cross-sectional design, 120 sets of parents of 60 children (n = 30 with obesity, age range 6–11) were recruited by local paediatricians. Parents completed the Parental Reflective Functioning Questionnaire. Children's and parents’ weight (assessed by BMI), as well as their socio-economic status (SES), were assessed to explore the contribution of PRF in the prediction of children's weight, controlling for parents’ weight and SES. RESULTS: t-test showed significant differences with medium effect sizes in BMI, SES and PRF between parents of children with and without obesity. The best model resulted from hierarchical multiple regression analyses and showed that mothers’ PRF predicted children's BMI above and beyond the prediction by parents’ BMI and SES. CONCLUSIONS: Low maternal PRF could be an important target for intervention strategies, highlighting the need to consider parental responses to children's emotions in the treatment of childhood obesity, particularly in parents with low SES and high BMI.